Renal effects of an emergency department chloride‐restrictive intravenous fluid strategy in patients admitted to hospital for more than 48 hours. (8th June 2017) - Yunos, Nor'azim Mohd; Bellomo, Rinaldo; Taylor, David McD; Judkins, Simon; Kerr, Fergus; Sutcliffe, Harvey; Hegarty, Colin; Bailey, Michael
Abstract: Objective: Patients commonly receive i.v. fluids in the ED. It is still unclear whether the choice of i.v. fluids in this setting influences renal or patient outcomes. We aimed to assess the effects of restricting i.v. chloride administration in the ED on the incidence of acute kidney injury (AKI). Methods: We conducted a before‐and‐after trial with 5008 consecutive ED‐treated hospital admissions in the control period and 5146 consecutive admissions in the intervention period. During the control period (18 February 2008 to 17 August 2008), patients received standard i.v. fluids. During the intervention period (18 February 2009 to 17 August 2009), we restricted all chloride‐rich fluids. We used the Kidney Disease: Improving Global Outcomes (KDIGO) staging to define AKI. Results: Stage 3 of KDIGO‐defined AKI decreased from 54 (1.1%; 95% confidence interval [CI] 0.8–1.4) to 30 (0.6%; 95% CI 0.4–0.8) ( P = 0.006). The rate of renal replacement therapy did not change, from 13 (0.3%; 95% CI 0.2–0.4) to 8 (0.2%; 95% CI 0.1–0.3) ( P = 0.25). After adjustment for relevant covariates, liberal chloride therapy remained associated with a greater risk of KDIGO stage 3 (hazard ratio 1.82; 95% CI 1.13–2.95; P = 0.01). On sensitivity assessment after removing repeat admissions, KDIGO stage 3 remained significantly lower in the intervention period compared with the control period ( P = 0.01). Conclusion: In a before‐and‐after trial, a chloride‐restrictive strategy in an ED was associated with a significant decrease in the incidence of stage 3 of KDIGO‐defined AKI.